Would Be Smart Balinese Cities (Indonesia): An Exploratory Case Study - Madakam, Somayya (Journal of Information Systems and Technology Management, 2020)
The word “Smart Cities” is new buzzword in every corner of the world. Many countries across the continents are trying to plant new smart cities or in the conversion process of existing cities. Bali (Indonesia) also seems to be in a conversion process of its Brown Field Cities. This research manuscript attempts to explore the Bali (Island) as a Smart Island regarding Smart Environment, Smart Economy, Smart Governance, Smart Mobility, Smart Living and Smart People dimensional perspective. This research manuscript has adopted a triangulation method for thematic narration since the study is qualitative and case study. The study explored that Bali/Balinese cities is/are still baby stepping of smart cities plantations. There needs to be a lot of work has to be done to become Smart Bali Island. The findings will help the Bali government to understand how far they could become full-fledged Smart Island by providing the Quality of Life to citizens and economic development of Balinese cities.